Study of hereditary non-syndromic ophthalmic pathology of child population of the Karachay-Cherkess Republic: features and structure of nosological spectrum - V.V. Kadyshev; A.V. Marakhonov; S.I. Kutsev; R.A. Zinchenko (РМЖ "Клиническая офтальмология")
V.V. Kadyshev1, A.V. Marakhonov1, S.I. Kutsev1,2, R.A. Zinchenko1,3 1 Research Centre of Medical Genetics of the Russian Academy of Medical Sciences, Moscow,  Russian Federation 2 Pirogov Russian National Research Medical University, Moscow, Russian Federation 3 M.F. Vladimirsky Moscow Regional Research and Clinical Institute (MONIKI), Moscow,   Russian Federation The publication is a continuation of the previously submitted data on the study of the epidemiology of ophthalmic diseases in children of the Karachay-Cherkess Republic. Genetic and epidemiological study of the population includes a research of a wide range of indicators. A burden assessment of the hereditary ocular pathology of the child population of the surveyed region and the data of molecular genetic diagnostics were published earlier. This article presents structure and features of a nosological spectrum of the visual organ hereditary pathology. Aim: to study the nosological spectrum and its features of hereditary non-syndromic ophthalmic pathology among the child population of the Karachay-Cherkess Republic. Patients and Methods: 90793 children from 10 regions of the Karachay-Cherkess Republic between the ages of 0 and 18 were examined, of which 121 people were enrolled in set. To solve the problem, genetic and epidemiological, clinical, paraclinical examination methods were used. Results: the structure and features of the nosological spectrum of non-syndromic hereditary ophthalmic pathology were determined in the child population of 10 regions of the Karachay-Cherkess Republic and the city of Cherkessk. Congenital malformations of the visual organ and hereditary pathology of the posterior segment of an eye (58%) make the main contribution to the prevalence. An overall prevalence of hereditary ocular pathology was at ratio 1:671. It was revealed that a large proportion of hereditary diseases of the visual organ with an autosomal dominant inheritance pattern (1:1163). The prevalence of autosomal recessive pathology was at ratio 1:2268 of people. Conclusion: autosomal dominant diseases make a greater contribution to the structure of the nosological spectrum — 1:1163. Congenital malformations of the visual organ and pathology of the posterior segment of the eye are prevalent in the structure of the pediatric nosological spectrum. Key words: epidemiology, genetics, hereditary pathology, nosological spectrum, children, Karachay-Cherkess Republic. For citation: Kadyshev V.V., Marakhonov A.V., Kutsev S.I., Zinchenko R.A. Study of hereditary non-syndromic ophthalmic pathology of child population of the Karachay-Cherkess Republic: features and structure of nosological spectrum. Russian Journal of Clinical Ophthalmology. 2019;19(1):7–12. About the authors:  1Vitalii V. Kadyshev — MD, PhD, Senior Researcher of the Laboratory of Genetic Epidemiology;  1Andrei V. Marakhonov — PhD, Biology, Senior Researcher of the Laboratory of Genetic Epidemiology;  1,2 Sergei I. Kutsev — MD, PhD, Professor, Сorresponding Member of RAS, Head of the Research Centre of Medical Genetics, Head of the Department of Molecular and Cell Genetics;  1,3Rena A. Zinchenko — MD, PhD, Professor, Deputy Director of the Scientific and Clinical Study, Head of the Laboratory of Genetic Epidemiology.  1Research Center of Medical Genetics. 1, Moskvorechie str., Moscow, 115522, Russian Federation.  2Pirogov Russian National Research Medical University. 1, Ostrovityanova str., Moscow, 117997, Russian Federation.  3Moscow Regional Research and Clinical Institute. 61/2, Shchepkina str., Moscow, 129110, Russian Federation.  Contact information: Vitalii V. Kadyshev, e-mail: vvh.kad@gmail.com. Financial Disclosure: no author has a financial or property interest in any material or method mentioned. There is no conflict of interests. Received 06.12.2018.